Socio cultural Barriers to Empowerment of Female University Teachers: An Exploratory Factor Analysis - Fouzia Shahin, Ra’ana Malik (PJE, 2023)
The study aimed to build an indigenous scale for measuring sociocultural barriers impeding female academics' empowerment in public universities in Punjab. For this objective, the researcher explored the sociocultural factors impacting female teachers' empowerment status while focusing on the personal, family, workplace, and public domains. A 5-point Likert scale questionnaire was prepared. After pretesting, 21 items were retained for conducting an Exploratory Factor Analysis. A sample was selected through simple random sampling from public universities in Punjab, and data were collected from 224 female academics through Online Survey. Using SPSS (version 25), EFA grouped items into four factors: (a) workplace harassment, (b) coercion on personal decisions, (c) domestic violence, and (d) negative public attitude. The cumulative scores on these four factors were added to the Sociocultural Barriers scale. All factors contributed to measuring the construct of sociocultural barriers as there was a positive correlation between factors and total scale scores. However, a weaker inter-factorial correlation indicated the mutual independence of each component. Scale reliability was α= 0.83, and the range of Alpha Coefficients for factors varied between 0.90-0.85.